PENERAPAN MESIN PENGERING KAYU BERBAHAN BAKAR HYBRID UNTUK MEMPERCEPAT PROSES PRODUKSI RUMAH ADAT MINAHASA - Mamengko, Alvito (Departemen Teknologi Pertanian Universitas Hasanuddin, 2024)
Minahasa traditional house is one of the characteristics of North Sulawesi Province, the potential of Indonesian natural resources in the form of wood is very potential to be used as a building material. Wood has features when used as a building material, such as being flexible, not easily broken when exposed to vibration loads due to earthquakes, has a beautiful appearance pattern to be used as decoration material, does not experience corrosion due to high humidity in the tropics, and other advantages. In addition, wood is also easily available around us so the price is relatively low compared to other structural building materials such as iron, steel, aluminum, and others. CV.Gloria is one of the Minahasa traditional house craftsmen, in making Minahasa traditional houses, of course, several criteria are needed for wood raw materials including wood that is ready to use must be dry and minimal moisture content, therefore the Wood Dryer PKM-PI team sees this situation as a problem, one of the factors inhibiting wood drying includes very high rainfall in North Sulawesi Province, from that problem the team aims to create a wood drying machine, utilizing a heat transfer system and utilizing used oil waste and powder from wood shavings.